A Decade of XBRL Research in Accounting in Indonesia: A Literature Study - Saragih, Arfah Habib; Soraya, Andini; Hendrawan, Adang (The Indonesian Journal of Accounting Research, 2021)
XBRL research in Indonesia has only begun to show its existence after a decade of the presence of this technology, which is around 2010. This phenomenon in Indonesia has motivated researchers to look at the history of the development of XBRL research as a subarea of accounting in Indonesia in bibliographic form over a period of one decade. Researchers are trying to describe the development of XBRL research in Indonesia and review the possible potential for XBRL research in Indonesia in the future. XBRL research topics in Indonesia are divided into four areas, namely its influence on business, adoption, technology development, and XBRL education. Based on the results of the review, XBRL research in Indonesia is still limited in using empirical research with quantitative methods. This study could be a relevant illustration of how the adoption of XBRL technology in developing countries such as Indonesia. This comprehensive literature review could enrich the knowledge thus inspiring other countries which may be at the same stage as Indonesia in adopting this technology in the business environment.